2012
DOI: 10.1111/j.1651-2227.2012.02624.x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of subgroups of monosymptomatic enuresis according to prepulse inhibition of the startle reflex

Abstract: The presented data provide evidence that PPI allows to identify two subgroups of ME. The results offer further insight into (at least) two different pathomechanisms involved in ME: (i) a maturational delay of reflex inhibition with reduced PPI and (ii) a normal PPI, possibly with abnormal sleep patterns, that can be influenced by imipramine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Levenga et al 2011; Olmos-Serrano et al 2011), and towards the diagnostic and pathophysiological dissociation of clinical subtypes (e.g. Eggert et al 2012). …”
Section: Update Of Recent Ppi Findings Of Relevance To Tsmentioning
confidence: 99%
“…Levenga et al 2011; Olmos-Serrano et al 2011), and towards the diagnostic and pathophysiological dissociation of clinical subtypes (e.g. Eggert et al 2012). …”
Section: Update Of Recent Ppi Findings Of Relevance To Tsmentioning
confidence: 99%
“…The reported increase in previously reduced PPI through DDAVP would then explain the clinical improvement through DDAVP in the children with nmE as well as offer an explanation for the absent treatment effect in children with mE . An additional study investigating changes in both native and distracted PPI through DDAVP could confirm these findings if the treatment lifted both levels comparatively.…”
Section: Discussionmentioning
confidence: 82%
“…The daytime urge may be compensated, avoiding daytime incontinence and leading to the diagnosis of monosymptomatic enuresis. In a recent study focusing on more subtle daytime symptoms as urge or small voided volumes and taking into account the effectiveness of DDAVP treatment, significantly different PPIs were found in subgroups with missing treatment effect of DDAVP and no evidence of any daytime symptoms and good therapeutic effect of DDAVP and some signs of daytime urge (without daytime incontinence) . While the former had normal PPIs compared with healthy controls, the later group showed the reduced PPI reported by Ornitz .…”
Section: Introductionmentioning
confidence: 94%
“…The authors concluded that high cortical mechanisms are relevant in prepulse inhibition and so play a role in the pathogenesis of NE. Prepulse inhibition was also reduced after attended prestimuli in children with ADHD . Additionally, Ornitz et al.…”
Section: Discussionmentioning
confidence: 90%
“…Eggert et al. identified two subgroups of children with NE: one subgroup with reduced prepulse inhibition and good desmopressin response and another group with normal prepulse inhibition and nonresponse. A recent combined prepulse inhibition and functional magnetic resonance imaging study demonstrated a pronounced prefrontal activation in healthy controls compared to children with monosymptomatic NE .…”
Section: Discussionmentioning
confidence: 99%